A 200 KYR RECORD OF COSMOGENIC RADIONUCLIDE PRODUCTION RATE AND GEOMAGNETIC FIELD INTENSITY FROM 10BE IN GLOBALLY STACKED DEEP-SEA SEDIMENTS - Frank M.; Schwarz B.; Baumann S.; Kubik P.W.; Suter M.; Mangini A. (My University, 1997)
The reconstruction of geomagnetic field intensity variations during the last 200 kyr from paleomagnetic data is at present the subject of numerous studies and major debate. There is currently no generally accepted record. Here we present a global stacked record of (230Thex-normalized) 10Be deposition in marine sediments representing relative variations in 10Be production rate which are translated into field intensity variations. The record shows major periods during which the field intensity was between 10% and 40% of the present day value; namely 30-42, 60-75, 85-110 and 180-192 kyr B.P. Our results are compared to independently derived paleomagnetic studies and Th/U calibrations of 14C dates on corals. During most of the observed period the geomagnetic field intensity was weaker than today, resulting in an overall 30% reduced value for the last 200 kyr.
Keywords: GEOMAGNETIC FIELD INTENSITY; BE-10 PRODUCTION RATE; SEDIMENT REDISTRIBUTION; TH-230 NORMALIZATION; BE-10 BOUNDARY SCAVENGING